Can the Combination of Acute Alcohol Intake and One Night of Sleep Deprivation Affect Neuromuscular Performance in Healthy Male Adults? A Cross-over Randomized Controlled Trial. Issue 5 (May 2019) - Rodrigues, Rodrigo; de Azevedo Franke, Rodrigo; Teixeira, Bruno C.; Cauduro Oliveira Macedo, Rodrigo; Diefenthaeler, Fernando; Baroni, Bruno M.; Vaz, Marco Aurélio
Abstract : Abstract: Rodrigues, R, Franke, RA, Teixeira, BC, Macedo, RCO, Diefenthaeler, F, Baroni, BM, and Vaz, MA. Can the combination of acute alcohol intake and one night of sleep deprivation affect neuromuscular performance in healthy male adults? A cross-over randomized controlled trial. J Strength Cond Res 33(5): 1244–1251, 2019—The aim of this work was to perform a cross-over study to compare isolated and combined effects of alcohol intake and sleep deprivation on neuromuscular responses. Ten young and physically active male subjects were allocated to 4 conditions: (a) placebo intake + normal sleep (PLA + SLE); (b) alcohol intake + normal sleep (ALC + SLE); (c) placebo intake + sleep deprivation (PLA + SDP); and (d) alcohol intake + sleep deprivation (ALC + SDP). In each condition, volunteers ingested 1 g of alcohol per kg of body mass of alcoholic beer or nonalcoholic beer (placebo), followed by one night of normal sleep or sleep deprivation. In the next morning, neuromuscular performance (knee extensor isometric and concentric peak torque and time to task failure during the endurance test) and muscle activation were assessed. No differences were observed in the neuromuscular performance. We observed a significant reduction in quadriceps activation during the knee extensor isometric test in ALC + SDP compared with PLA + SLE (−20.8%; p = 0.02; d = 0.56). Our results demonstrated that acute alcohol intake and one night of sleep deprivation reduced quadriceps muscle activation without impact on neuromuscular performance.